Dual use of Diff-Quik-like stains for the simultaneous evaluation of human sperm morphology and chromatin status - Sousa, AP (2011)
BACKGROUND: Sperm chromatin status and nuclear DNA damage can be detected using well-established assays. However, most techniques are time-consuming and/or involve elaborate protocols and equipment. We have recently developed a simple and fast method to monitor sperm chromatin status in field conditions using the Diff-Quik assay which is employed in fertility clinics to assess sperm morphology with standard bright field microscopy. In the present study, we demonstrate that any Diff-Quik-like stain can easily, reproducibly and routinely monitor human sperm chromatin status as well. METHODS: Different Diff-Quik-like stains were used to assess sperm morphology and the presence of abnormal dark nuclear staining in human sperm from four ART centres. The TUNEL assay was performed in the same samples, and fertility outcomes were assessed. RESULTS: A significant correlation was found between TUNEL-positive sperm and dark sperm nuclei. Moreover, associations were also found between the percentage of dark sperm nuclei and seminal parameters, embryo development rate, embryo quality and clinical pregnancy, as well as with cryptorchidism, and there was a tendency towards an association with age. A value of 32% abnormal staining is suggested as a predictive threshold for embryo development and pregnancy. CONCLUSIONS: Our results show that any Diff-Quik-like stain, already implemented in most laboratories to assess sperm morphology, can be adapted as an indicator for chromatin status in human sperm.